Tindak Tutur Guru dan Siswa dalam Pembelajaran Bahasa Indonesia - Nelvia Susmita (JPGI (Jurnal Penelitian Guru Indonesia), 2019)
This research aims to describe the speech act of locussion, illocussion, and perlocussion in Bahasa Indonesia subject for students grade X SMAN 8 Kerinci. Speech act is a crucial aspect which is used in the teaching and learning process in the classroom. Therefore, it is important to concern the use of speech act done by both teachers and the students in order to accomplish the learning goals. The theories used to analize the speech act of the teachers and students in the learning process of Bahasa Indonesia subject in this research are proposed by Nadar (2008), Suadi (2014), Chaer (2010), Bonodari (20115), and Rehardi (2005). The type of this research is qualitative research. The subject of the research are teachers and students grade X in SMaN 8 Kerinci in the process of teaching and learning in Bahasa Indonesia subject. The technique of data collection are namely listening freely and speaking involved, recording techinque, and writing down technique. The technique of data analysis is equal pragmatics. The result of the research can be described as follow: it is found the speech act in form of locussion, illocussion, and perlocussion. The speech act of locussion includes the forms of news, questions forms and commands forms. The speech act of illocussion includes assertive illocussion, directive, expressive, commisive, and declarative. The speech act of perlocussion that was found is giving influences.